Analisis Kelayakan Finansial dan Strategi Pengembangan Usaha Peternakan Itik Mojosari - Amam, Amam; Ramadhan, Alvian Madafiqiya (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Duck farming is one of the main livelihoods for some people in Modopuro Village, Mojosari Sub-District, Mojokerto District, so that the area has become one of the centers for developing Mojosari ducks. This study aims to analyze the financial feasibility and formulate a strategy for developing Mojosari duck farming. This study uses a descriptive and quantitative descriptive analysis approach. Data collection was carried out using observation methods, Focus Group Discussions (FGD), interviews, and filling out questionnaires. This study involved 1 (one) group of farmers consisting of 50 respondents. Data analysis used quantitative descriptive in the form of financial feasibility and IFAS, EFAS, and SWOT analysis. The results of the study showed that the Mojosari duck farming business had a B/C Ratio value of 0.43 and an R/C Ratio value of 1.25. The results of the IFAS-EFAS analysis showed an internal factor value of 3.02 and an external factor value of 3.15, indicating that the Mojosari duck farming business was in quadrant I, namely growth and development strategies. The recommended alternative strategies are product diversification, duck eggs into salted eggs to increase added value and competitiveness of farmer groups, utilizing family support and technology to market salted eggs, expanding marketing networks, establishing cooperatives and farmer corporations to increase farmer bargaining power.